The benefit-risk analysis of omega-3 polyunsaturated fatty acids and heavymetals in seven smoked fish species from Siberia - Gladyshev, M. I.; Anishchenko, O. V.; Makhutova, O. N.; Kolmakova, O. V.; Trusova, M. Y.; Morgun, V. N.; Gribovskaya, I. V.; Sushchik, N. N. (Journal of Food Composition and Analysis, 2020)
In cold smoked species of genus Coregonus, identified by molecular genetic analysis, contents of fatty acids and heavy metals and arsenic were measured. The highest content of sum of long-chain polyunsaturated fatty acids of omega-3 family (LC-PUFA), namely eicosapentaenoic (EPA) and docosahexaenoic (DHA) fatty acids, 6.53 ± 0.78 mg g−1 wet weight, was characteristic of tugun Coregonus tugun. This is the first quantitative estimation (mg LC-PUFA per g of product) of the nutritive value of smoked fish. Thus, to obtain a daily personal doze of EPA + DHA of 1 g, recommended for prevention of cardiovascular diseases, one needs to consume 153 g of the smoked tugun. Metals contents did not exceed standards for fish meat except Pb in least cisco Coregonus sardinella. Accordingly, values of hazard quotients, which estimate benefit-risk ratio of fish intake, indicate that most of the smoked fish species are safe product for human nutrition, except least cisco regarding Pb content.